Analyzing the organizational questions of the elite youth academies by the case study of football academy of Debrecen - Szalánczi, Zoltán (Applied Studies in Agribusiness and Commerce, 2020)
Thanks to the effect of the resources flown in to the youth football, the previous, and more simpler structural scheme of the clubs went under a transformation. I will analyse the operation of the youth sport enterprises as economic companies, and the organizational scheme with the most important managerial questions faced in the firm. This will be based on the case study of the Football Academy of Debrecen. In the first part of my publication, I will investigate the evolution and the importance of the sport enterprises, with the relevant scientific literature. In the second part I will discuss the structural scheme of the Football Academy of Debrecen with the analysis of the separate departments. I will search for the differences between the youth sport enterprises and the organisations who are operating as a professional football club. JEL code: Z2